Asymmetric 1, 4‐Addition of Arylboronic Acids to β, γ‐Unsaturated α‐Ketoesters using Heterogeneous Chiral Metal Nanoparticle Systems. Issue 2 (5th December 2019) - Miyamura, Hiroyuki; Yasukawa, Tomohiro; Zhu, Zhiyuan; Kobayashi, Shū
Abstract: Asymmetric 1, 4‐addition reactions with β, γ‐unsaturated α‐ketoesters are valuable because the resulting chiral ketoester compounds can be converted into various useful species that are often used as chiral building blocks in drug and natural product synthesis. However, β, γ‐unsaturated α‐ketoesters have two reactive points in terms of nucleophilic additions, which will lead to the 1, 4‐adduct, the 1, 2‐adduct and to the combined 1, 4‐ and 1, 2‐adduct. Therefore, controlling this chemoselectivity is an important factor for the development of these transformations. Here, we developed an asymmetric 1, 4‐addition of aryl boronic acids to β, γ‐unsaturated α‐ketoesters by using heterogeneous chiral rhodium nanoparticle systems with a chiral diene ligand bearing a secondary amide moiety. The newly developed polydimethylsilane‐immobilized rhodium nanoparticle catalysts showed high activity, high chemoselectivity, and excellent enantioselectivity, and this is the first heterogeneous catalytic system for this asymmetric reaction. Metal nanoparticle catalysts were recovered and reused without loss of activity or leaching of metal. Abstract :